Method for measuring water-ash-material ratio of slurry in aluminum ash hydrolysis treatment and application

By measuring the water-cement material ratio of the slurry in aluminum ash hydrolysis treatment, and ion chromatography is used to calculate the raw material water volume and the semi-finished aluminum ash mass ratio, the problem of inaccurate measurement in the prior art is solved, and the normal operation and production safety of the water-cement batching system are achieved.

CN120334454APending Publication Date: 2025-07-18HENAN MINGTAI TECH DEV CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510337290.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

The prior art cannot accurately determine the material ratio of raw material water and semi-finished aluminum ash in the mixing tank, resulting in uneven mixing of aluminum ash with water, affecting the representativeness of the slurry, and thus affecting the accuracy of the measurement results. It is impossible to ensure the accurate material ratio of raw material ash and raw material brine in actual production.

Method used

A method for determining the water-cement material ratio of slurry in aluminum ash hydrolysis treatment is provided. By sampling and measuring the ion concentration in raw material water and slurry filtered brine, ion chromatography is used to calculate the raw material water volume and semi-finished aluminum ash mass ratio in the stirring tank, real-time monitoring of the material ratio in the batching tank and the reaction tank during production, and timely discovering and adjusting the faults of the water-cement material system.

Benefits of technology

The accurate determination of the water-cement material ratio of the slurry in the mixing tank is achieved, ensuring the normal operation of the water-cement material system, reducing the loss of ammonia dissolution, avoiding increased energy consumption and equipment safety risks, and meeting the precise needs of industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120334454A_ABST
    Figure CN120334454A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of salt slag aluminum ash application, and particularly relates to a method for measuring the water-ash-material ratio of slurry in aluminum ash hydrolytic treatment and application of the method for measuring the water-ash-material ratio of the slurry in the aluminum ash hydrolytic treatment. Taking the raw material water sample, the semi-finished product aluminum ash sample and a slurry filtered saline water sample obtained by filtering the slurry sample, determining the Cl <-> content of the semi-finished product aluminum ash sample, and determining Cl <-> and SO4 < 2-> in the raw material water sample and the slurry filtered saline water sample; f <->; and substituting the measured numerical value into a formula (1) to obtain the mass ratio of the volume of the raw material water to the mass of the semi-finished product aluminum ash in the stirring tank. According to the method, the material ratio of the water to the aluminum ash in the production can be accurately and rapidly measured, the material ratio of the raw material ash to the raw material saline water in the actual production is monitored, normal operation of the production is ensured, and the method has actual application value on aluminum ash treatment in industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the harmless treatment and high-value application of salt slag aluminum ash, and particularly relates to a method for determining the water-to-ash material ratio of slurry in the hydrolysis treatment of aluminum ash and its application. Background Art

[0002] In the process of aluminum production, the main components of the produced aluminum ash include substances with economic value such as aluminum oxide, aluminum nitride, aluminum carbide, aluminum sulfide, soluble salts, etc., and at the same time contain a certain amount of harmful elements. Therefore, the harmless and resourceful treatment of aluminum ash is an issue that enterprises need to consider. When aluminum ash encounters water, various chemical reactions will occur, generating substances such as aluminum hydroxide, ammonia, methane, hydrogen sulfide, etc. Through appropriate collection methods, gases such as ammonia, methane, and hydrogen sulfide generated by the hydrolysis reaction can be collected and further processed and utilized. The generated aluminum hydroxide can be recovered through steps such as filtration, washing, and drying, and used for the production of aluminum products or other chemical products. And the soluble salts in the aluminum ash can also be separated and recovered through methods such as evaporation crystallization for other industrial uses. The direct hydrolysis method of aluminum ash is one of the low-cost and harmless treatment methods, and it is also the basis and prerequisite for the high-value utilization of aluminum ash slag.

[0003] In the direct hydrolysis method of aluminum ash, it is necessary to mix raw material water and semi-finished ash in a stirring tank to form a slurry. Then, use a slurry pump to send the slurry in the stirring tank into the reaction tank for the hydrolysis reaction of aluminum ash. Since ammonia is highly soluble in water, when the hydrolysis reaction occurs between aluminum ash and water in the reaction tank, the generated ammonia will also be highly soluble in the water of the slurry, resulting in a decrease in the recovered ammonia volume. Therefore, it is necessary to stabilize the ratio of water and ash materials during the hydrolysis of aluminum ash and water in the reaction tank, and reduce the absorption of ammonia by the slurry formed by mixing aluminum ash and water. According to actual work experience, when the volume ratio of raw material water to the mass of semi-finished aluminum ash is 1.5:1, the dissolution amount of ammonia by the slurry formed by mixing aluminum ash and water is small, and the generated ammonia is exported from the aluminum ash reaction tank and enters the ammonia absorption tower for absorption. Moreover, when the ratio of water to aluminum ash materials is 1.5:1, aluminum ash and water are mixed in the stirring tank to form a slurry. At this time, the soluble salts in the aluminum ash are almost dissolved in the slurry; after the hydrolysis reaction is completed in the reaction tank, filter the slurry in the reaction tank to recover the filtered brine and the remaining reactants. At this time, the salt content in the slurry filtered brine is close to saturation, and the amount of water to be evaporated during MVR evaporation crystallization is small, and the energy consumption is small. When the raw material water is excessive, it means that there is excessive water in the slurry, and the generated ammonia is highly soluble in the slurry and cannot be exported from the aluminum ash reaction device for recovery, but is dissolved in the slurry filtered brine. During the evaporation crystallization process, the ammonia dissolved in the slurry filtered brine overflows when heated and enters the air to pollute the air; in addition, and there is excessive water in the slurry. During MVR evaporation crystallization, a large amount of water needs to be evaporated, and the energy consumption is large. Therefore, when the raw material water is excessive, it will cause air pollution and high energy consumption during the hydrolysis and utilization of aluminum ash. In addition, when the raw material water is too little, it means that there is too little water in the slurry, the soluble salts in the aluminum ash cannot be completely dissolved in the raw material water, and aluminum ash and water cannot form a slurry, and the aluminum ash will agglomerate, which may seriously cause pipeline blockage and make production impossible to proceed. A small amount of raw material water means that the concentration of the reactants is relatively high, which may lead to an accelerated reaction rate and the reaction is too intense. In the reaction tank, if the reaction is too intense, a large amount of heat and gas may be generated, increasing the risk of explosion and equipment damage, and affecting the safety of the stirring tank. In summary, the ratio of the volume of raw material water to the mass of semi-finished aluminum ash being 1.5:1 is very important. Usually, the preset ratio of the volume of raw material water to the mass of semi-finished aluminum ash is 1.5:1. The ratio range of the volume of raw material water to the mass of semi-finished aluminum ash measured in actual production in the stirring tank can be between 1.4 and 1.6. At this time, the water-ash batching system of raw material water and semi-finished aluminum ash operates normally and can produce normally.

[0004] In the prior art, when measuring the ratio of water to aluminum ash, the method adopted is: take a semi-finished ash sample at the feeding port of the stirring tank and analyze the soluble salt content in the semi-finished ash sample; use a plastic measuring cup to take about 200 ml of the slurry sample in the stirring tank at the sewage discharge port of the stirring tank and weigh the gross weight M 毛 , filter the slurry with a vacuum filter, clean the measuring cup, and dry it and weigh the weight of the measuring cup as M杯 All the washed slurry is filtered by a vacuum filter, and the filtered slurry cake is rinsed with pure water 3 times. Filter until no liquid drips from the bottom of the funnel, take out the filtered slurry cake, dry it at 110 °C for 2 h, and weigh the dry slurry cake as M. 饼 ,

[0005] Then the weight of the original semi-finished product ash corresponding to the dry slurry cake is M 饼 / (1 - salt content%);

[0006] The weight of water in the slurry is M 毛 - M 杯 - M 饼 / (1 - salt content%)

[0007] The ratio of water to aluminum ash is: [M 毛 - M 杯 - M 饼 / (1 - salt content%)]: [M 饼 / (1 - salt content%)]

[0008] However, the disadvantage of the above measurement method is that not all of the aluminum ash can dissolve in water, and it is impossible to ensure complete and uniform mixing of the aluminum ash and water in the stirring tank. Because the aluminum ash has a tendency to settle, it is difficult to ensure complete and uniform mixing of the aluminum ash and water during the stirring process. This non-uniformity will affect the representativeness of the slurry, resulting in the slurry sample taken from the plastic measuring cup not being able to truly represent the stirring tank, and further affecting the accuracy of the measurement results. The existing methods cannot accurately calibrate the material ratio of the raw material ash and the raw material brine in actual production to ensure the accuracy of actual production. Summary of the Invention

[0009] The present invention provides a method for measuring the water-to-ash material ratio of slurry in the hydrolysis treatment of aluminum ash and its application to solve the problem that the existing technology cannot accurately measure the material ratio of the raw material water and the semi-finished aluminum ash in the stirring tank to ensure the accuracy of actual production. It can accurately measure the ratio of the volume of raw material water to the mass of semi-finished aluminum ash in the stirring tank and the reaction tank during production, monitor in real time the ratio of the actual volume of raw material water to the mass of semi-finished aluminum ash in the batching tank and the reaction tank during production, timely detect faults in the water-ash batching system, ensure the normal operation of the water-ash batching system, and meet the normal operation of production.

[0010] To solve the above problems, the technical solution of the present invention is:

[0011] The present application provides a method for measuring the water-to-ash material ratio of slurry in the hydrolysis treatment of aluminum ash, including the following steps:

[0012] S1: Feed raw water and semi-finished aluminum ash into a stirring tank according to a preset material ratio for mixing to obtain a slurry, and then feed the slurry into a reaction tank for the hydrolysis reaction of the semi-finished aluminum ash; after the reaction is completed, the remaining slurry is discharged from the reaction tank, and the reacted slurry is separated into solid and liquid to obtain hydrolysis residues and filtered brine;

[0013] The semi-finished aluminum ash is a powder obtained by ball-milling and screening the raw aluminum ash and removing the aluminum-containing particles;

[0014] Wash the hydrolysis residues, and use the water after washing as raw water;

[0015] S2: Take samples in sequence: take a raw water sample, take a semi-finished aluminum ash sample, and take a slurry sample;

[0016] Filter the slurry sample to obtain a slurry-filtered brine sample;

[0017] S3: Determine the Cl - content in the semi-finished aluminum ash sample;

[0018] Determine the density of the raw water sample, and determine the mass concentrations of Cl - , SO4 2- , F - , NO3 - in the raw water sample;

[0019] Determine the density of the slurry-filtered brine sample; and determine the mass concentrations of Cl - , SO4 2- , F - , NO3 - in the slurry-filtered brine sample;

[0020] S4: Substitute the values measured in S3 into formula (1) to obtain the volume ratio of raw water to the mass of semi-finished aluminum ash in the stirring tank as V 原 / M:

[0021]

[0022] (In formula (1):

[0023] V 原 is the volume (L) of raw water in the stirring tank;

[0024] M is the weight (Kg) of semi-finished ash in the stirring tank;

[0025] a is the Cl - ion content (g / Kg) in the semi-finished ash;

[0026] ρ 原 is the density (g / L) of the raw water sample;

[0027] b is the Cl ion content (g / L) in the raw water; -

[0028] d 原 is the SO4 ion content (g / L) in the raw water; 2-

[0029] e 原 is the F ion content (g / L) in the raw water; -

[0030] f 原 is the NO3 ion content (g / L) in the raw water; -

[0031] ρ 滤 is the density (g / L) of the slurry-filtered brine sample

[0032] c is the Cl ion content (g / L) in the slurry-filtered brine; -

[0033] d 滤 is the SO4 ion content (g / L) in the slurry-filtered brine; 2-

[0034] e 滤 is the F ion content (g / L) in the slurry-filtered brine; -

[0035] f 滤 is the NO3 ion content (g / L) in the slurry-filtered brine; -

[0036] Furthermore, the fineness of the semi-finished aluminum ash particles is less than 80 mesh.

[0037] Furthermore, the ratio of the volume of the raw water to the mass of the semi-finished aluminum ash in the preset ratio is 1.5:1.

[0038] Furthermore, the determination method for the mass concentrations of Cl, SO4, F, and NO3 in the semi-finished aluminum ash sample, the raw water sample, and the slurry-filtered brine sample is ion chromatography. - content, Cl - , SO4 2- , F - , NO3 - in the raw water sample and Cl - , SO4 2- , F - , NO3 - in the slurry-filtered brine sample is ion chromatography.

[0039] ​​​​​​​​The present application also provides a method for measuring the water-to-ash material ratio of the slurry in the hydrolysis treatment of aluminum ash, which is applied to the water-ash batching system during the hydrolysis treatment of aluminum ash. The actual ratio of the volume of raw water and the mass of semi-finished aluminum ash in the batching tank and the reaction tank during production is monitored in real time to promptly detect faults in the water-ash batching system, ensure the normal operation of the water-ash batching system, and meet the normal operation of production.

[0040] Further, it includes the following steps:

[0041] When the V 原 / M ratio ranges from 1.4 to 1.6, it indicates that the water-ash batching system is operating normally;

[0042] When the V 原 / M ratio is greater than 1.6 or less than 1.4, it indicates that the water-ash batching system is not operating properly. Stop feeding, detect the water-ash batching system, calibrate the weight of the semi-finished ash discharged and the inflow of raw water, and after calibration and stabilization, take another sample for analysis and detection of the V 原 / M ratio; if the V 原 / M ratio ranges from 1.4 to 1.6, it indicates that the water-ash batching system is operating normally after adjustment; if the V 原 / M ratio is still greater than 1.6 or less than 1.4, repeat the above adjustment steps until the V 原 / M ratio ranges from 1.4 to 1.6 and the water-ash batching system is operating normally

[0043] Through the above technical solutions, the beneficial effects of the present invention are:

[0044] (1) By measuring the ratio of the volume of raw water and the mass of semi-finished aluminum ash in the slurry during production, the present application accurately measures the water-to-ash material ratio of the slurry in the mixing tank, monitors the water-to-ash material ratio in the batching tank and the reaction tank during production in real time, promptly detects faults in the water-ash batching system, and ensures the normal operation of the water-ash batching system. The method of the present application is easy to operate and has practical application value for the treatment of aluminum ash in industrial production.

[0045] (2) The mass concentrations of Cl - , SO4 2- , F - , NO3 - in the raw water sample and the filtered brine sample of the slurry, and the chloride ion content in the soluble part of the semi-finished aluminum ash sample are measured by ion chromatography, and the measurement results are more accurate. Description of the Drawings

[0046] Figure 1 is a schematic diagram of the mixing process of the raw water and semi-finished aluminum ash of the present invention; Detailed Embodiments

[0047] A method for determining the water-to-ash material ratio of slurry in the hydrolysis treatment of aluminum ash, comprising the following steps:

[0048] S1: Raw water and semi-finished aluminum ash are fed into a stirring tank according to a preset material ratio for mixing to obtain a slurry, and then the slurry is sent into a reaction tank for the hydrolysis reaction of the semi-finished aluminum ash; after the reaction is completed, the remaining slurry is discharged from the reaction tank, and the solid-liquid separation of the reacted slurry is carried out to obtain hydrolysis residues and filtered brine;

[0049] The semi-finished aluminum ash is powder particles obtained by ball milling and screening the raw aluminum ash and removing the aluminum-containing particles;

[0050] The hydrolysis residues are washed with water, and the water after washing is used as raw water; the raw water contains NaCl, Na2SO4, NaF, KCl, and NaNO3;

[0051] S2: Sampling is carried out in sequence: taking a raw water sample, taking a semi-finished aluminum ash sample, and taking a slurry sample;

[0052] The slurry sample is filtered to obtain a slurry filtered brine sample;

[0053] S3: Determine the Cl - content in the semi-finished aluminum ash sample;

[0054] Determine the density of the raw water sample, and determine the Cl - , SO4 2- , F - , NO3 - mass concentration in the raw water sample;

[0055] Determine the density of the slurry filtered brine sample; and determine the Cl - , SO4 2- , F - , NO3 - mass concentration in the slurry filtered brine sample;

[0056] S4: Substitute the values measured in S3 into formula (1) to obtain the volume of raw water and the mass ratio of semi-finished aluminum ash in the stirring tank as V 原 / M:

[0057]

[0058] (In formula (1):

[0059] V 原 is the volume (L) of raw water in the stirring tank;

[0060] M is the weight (Kg) of semi-finished ash in the stirring tank;

[0061] a is Cl in the semi-finished ash -Ionic content (g / Kg);

[0062] ρ 原 is the density of the raw water sample (g / L);

[0063] b is the Cl - ionic content in the raw water (g / L);

[0064] d 原 is the SO4 2- ionic content in the raw water (g / L);

[0065] e 原 is the F - ionic content in the raw water (g / L);

[0066] f 原 is the NO3 - ionic content in the raw water (g / L);

[0067] ρ 滤 is the density of the slurry-filtered brine sample (g / L)

[0068] c is the Cl - ionic content in the slurry-filtered brine (g / L);

[0069] d 滤 is the SO4 2- ionic content in the slurry-filtered brine (g / L);

[0070] e 滤 is the F - ionic content in the slurry-filtered brine (g / L);

[0071] f 滤 is the NO3 - ionic content in the slurry-filtered brine (g / L).

[0072] Origin of formula (1): The soluble salt components in aluminum ash are: NaCl: 65 - 80%, KCl: 25 - 28%, Na2SO4: 0.1 - 1%, NaF: 0.11%, NaNO3: 0.01%. Both raw water, semi-finished aluminum ash, and slurry-filtered brine contain chlorine. The semi-finished aluminum ash is mixed with raw water to form a slurry, and the soluble salts in the mixed semi-finished aluminum ash dissolve in the raw water. According to the element conservation, the chlorine element in the slurry-filtered brine sample comes from the chlorine element in the raw water sample and the chlorine element in the soluble salts of the semi-finished aluminum ash sample. According to the mass conservation of chloride ions in the raw water sample, semi-finished aluminum ash sample, and slurry-filtered brine sample, formula (2) is obtained:

[0073] M×a + V 原 ×b = V 滤 c (2)

[0074] In formula (2):

[0075] M is the weight (kg) of the semi-finished ash in the mixing tank;

[0076] a is the Cl - ion content (g / kg) in the semi-finished ash;

[0077] V 原 is the volume (L) of the raw water in the mixing tank;

[0078] b is the Cl - ion content (g / L) in the raw water;

[0079] V 滤 is the volume (L) of the slurry filtration brine obtained by completely filtering the slurry theoretically;

[0080] c is the Cl - ion content (g / L) in the slurry filtration brine;

[0081] Mix V 原 L of raw water and M kg of semi-finished aluminum ash in the mixing tank to make a slurry. m kg of soluble salts in the aluminum ash dissolve in the slurry. Theoretically, completely filter the slurry to obtain V 滤 L of slurry filtration brine.

[0082] The mass of the slurry filtration brine = the mass of the raw water + the mass of the soluble salts in the aluminum ash

[0083] ρ 滤 V 滤 = ρ 原 V 原 + m

[0084] In this process, the slurry filtration brine is equivalent to directly adding solute (soluble salts) to the raw water. That is, compared with the raw water, the slurry filtration brine solution only has an increase in solute, and the solvent water in the solution does not change.

[0085] The mass of the solvent water in the raw water = the mass of the solvent water in the slurry filtration brine (3)

[0086] Since the chlorine element comes from NaCl and KCl in the soluble salts in the aluminum ash; according to the composition of the soluble salts in the aluminum ash, NaCl: 65 - 80%, KCl: 25 - 28%, Na2SO4: 0.1 - 1%, NaF: 0.11%, NaNO3: 0.01%, NaCl is selected to replace KCl. The raw material water is the water used for washing the hydrolysis residues; the raw material water contains a small amount of NaCl, Na2SO4, NaF, KCl, and NaNO3. Therefore, it is set that the chloride ions in the slurry filtration brine and the raw materials both come from the products of the ionization of NaCl, which are sodium ions (Na + ) and chloride ions (Cl - ) in which the chloride ions (Cl - ). The solutes in the raw material water are NaCl, Na2SO4, NaF, and NaNO3.

[0087] (1) Calculation of the mass of the solvent water in the raw material water

[0088] The mass of the raw material water = the mass of the solvent water in the raw material water + the mass of the solutes in the raw material water

[0089] Because the solutes in the raw material water are NaCl, Na2SO4, NaF, and NaNO3, the mass concentrations of NaCl, Na2SO4, NaF, and NaNO3 in the raw material water are measured.

[0090] The mass of the solutes in the raw material water can be obtained as ρ 原NaCl V 原 +ρ 原Na2SO4 V 原 +ρ 原NaF V 原 +ρ 原NaNO3 V 原 ;

[0091] Among them, V 原 is the volume (L) of the raw material water in the stirring tank; ρ 原NaCl is the mass concentration (g / L) of NaCl in the raw material water; ρ 原Na2SO4 is the mass concentration (g / L) of Na2SO4 in the raw material water; ρ 原NaF is the mass concentration (g / L) of NaF in the raw material water; ρ 原NaNO3 is the mass concentration (g / L) of NaNO3 in the raw material water;

[0092] The mass of the raw material water is ρ 原 V 原 , where ρ 原 is the density (g / L) of the raw material water;

[0093] That is, the mass of the solvent water in the raw material water = ρ 原 V 原 -ρ 原NaCl V原 -ρ 原Na2SO4 V 原 -ρ 原NaF V 原 -ρ 原NaNO3 V 原

[0094] (2) Calculation of the mass of solvent water in the slurry-filtered brine

[0095] The mass of the slurry-filtered brine = the mass of solvent water in the slurry-filtered brine + the mass of solute in the slurry-filtered brine

[0096] Since the solutes in the slurry-filtered brine are NaCl, Na2SO4, NaF, and NaNO3, measure the mass concentrations of NaCl, Na2SO4, NaF, and NaNO3 in the slurry-filtered brine.

[0097] Then the mass of the solute in the raw water can be obtained as ρ 滤NaCl V 滤 +ρ 滤Na2SO4 V 滤 +ρ 滤NaF V 滤 +ρ 滤NaNO3 V 滤 ;

[0098] Among them, V 滤 is the volume (L) of the slurry-filtered brine theoretically obtained by complete filtration of the slurry; ρ 滤NaCl is the mass concentration (g / L) of NaCl in the slurry-filtered brine; ρ 滤Na2SO4 is the mass concentration (g / L) of Na2SO4 in the slurry-filtered brine; ρ 滤NaF is the mass concentration (g / L) of NaF in the slurry-filtered brine; ρ 滤NaNO3 is the mass concentration (g / L) of NaNO3 in the slurry-filtered brine.

[0099] The mass of the slurry-filtered brine is ρ 滤 V 滤 where ρ 滤 is the density (g / L) of the slurry-filtered brine.

[0100] That is, the mass of solvent water in the slurry-filtered brine = ρ 滤 V 滤 -ρ 滤NaCl V 滤 -ρ 滤Na2SO4 V 滤 -ρ 滤NaF V 滤 -ρ 滤NaNO3 V 滤

[0101] Based on the mass of solvent water in the raw material water = the mass of solvent water in the slurry-filtered brine, the formula (4) is obtained

[0102] ρ 原 V 原 -ρ 原NaCl V 原 -ρ Na2SO4 V 原 -ρ 原NaF V 原 -ρ 原NaNO3 V 原 =ρ 滤 V 滤 -ρ 滤NaCl V 滤 -

[0103] ρ 滤Na2SO4 V 滤 -ρ 滤NaF V 滤 -ρ 滤NaNO3 V 滤 (4)

[0104] Express the mass concentrations of NaCl, Na2SO4, NaF, and NaNO3 in Equation (5) using the mass concentrations of Cl - ;SO4 2- ;F - ;NO3 - to obtain Equation (6); for example: where b is the Cl - ion content (g / L) in the raw material water.

[0105] ρ 原 ×V 原 -1.65bV 原 -1.48d 原 V 原 -2.2e 原 V 原 -1.37f 原 V 原 =ρ 滤 ×V 滤 -1.65cV 滤 -

[0106] 1.48d 滤 V 滤 -2.2e 滤 V 滤 -1.37f 滤 V 滤 (5)

[0107] In Equation (5):

[0108] V 原is the volume (L) of raw water in the mixing tank;

[0109] ρ 原 is the density (g / L) of the raw water sample;

[0110] b is the Cl - ion content (g / L) in the raw water;

[0111] d 原 is the SO4 2- ion content (g / L) in the raw water;

[0112] e 原 is the F - ion content (g / L) in the raw water;

[0113] f 原 is the NO3 - ion content (g / L) in the raw water;

[0114] V 滤 is the volume (L) of the slurry filtration brine theoretically obtained by completely filtering the slurry;

[0115] ρ 滤 is the density (g / L) of the slurry filtration brine sample

[0116] c is the Cl - ion content (g / L) in the slurry filtration brine;

[0117] d 滤 is the SO4 2- ion content (g / L) in the slurry filtration brine;

[0118] e 滤 is the F - ion content (g / L) in the slurry filtration brine;

[0119] f 滤 is the NO3 - ion content (g / L) in the slurry filtration brine.

[0120] Formula (6) is obtained from formula (5):

[0121]

[0122] Substitute formula (6) into formula (2) to obtain formula (1):

[0123]

[0124] a, b, c, d 原 、e 原 、f 原 、d 滤, e 滤 , f 滤 Determined by ion chromatography, the specific method is as follows:

[0125] (1) The determination and analysis steps of the mass fraction a of Cl⁻ ions in the semi-finished aluminum ash sample are as follows:

[0126] Weigh 1.000 g of semi-finished aluminum ash into a glass beaker, add 50 ml of water, stir for 3 min, filter it into a 100-ml volumetric flask, wash the filter paper three times with 30 ml of water into the 100-ml volumetric flask, and make up the volume to the mark with water, then shake well. Pipette 500 μl of the test solution into a 50-ml volumetric flask, make up the volume to the mark with water, and shake well. Use a syringe to pipette the diluted test solution into the ion chromatograph to analyze the Cl⁻ ion content (mg / L) in the syringe solution. The Cl⁻ ion content in the semi-finished ash is:

[0127] a = (Cl⁻ ion content (mg / L) in the injected test solution) * (0.05 / 0.5) * (100 / 1)

[0128] Number of determinations: Determine twice in parallel and take the average value.

[0129] (2) Raw water sample

[0130] Pipette 1 ml of raw water into a 100-ml volumetric flask, make up the volume to the mark with water, and shake well. Pipette 500 μl of the diluted raw water into a 50-ml volumetric flask, make up the volume to the mark with water, and shake well. Use a syringe to pipette the twice-diluted test solution into the ion chromatograph to analyze the Cl - , SO₄ 2- , F - , NO₃ - ⁻ ion content (mg / L). The Cl - , SO₄ 2- , F - , NO₃ - ⁻ ion content is:

[0131] b = (Cl - ⁻ ion content (mg / L) in the injected test solution) * (0.05 / 0.5) * 100

[0132] d 原 = (SO₄ 2- ⁻ ion content (mg / L) in the injected test solution) * (0.05 / 0.5) * 100

[0133] e 原 = (F - ⁻ ion content (mg / L) in the injected test solution) * (0.05 / 0.5) * 100

[0134] f 原=(Ionic content of NO3 in the injection test solution (mg / L)) * (0.05 / 0.5) * 100 - Ionic content (mg / L)) * (0.05 / 0.5) * 100

[0135] Number of determinations: Determine in parallel twice and take the average value.

[0136] (3) Take the slurry sample

[0137] Filter the slurry sample to obtain the filtered slurry brine sample. Pipette 1 ml of the filtered slurry brine sample into a 100 ml volumetric flask, make up to the mark with water, and shake well. Pipette 500 ul of the test solution into a 50 ml volumetric flask, make up to the mark with water, and shake well.

[0138] Use a syringe to pipette the twice-diluted test solution into the ion chromatograph to analyze the ionic contents of Cl - , SO4 2- , F - , NO3 - Ionic contents (mg / L) in the raw material. Cl in the raw material - , SO4 2- , F - , NO3 - Ionic contents are as follows:

[0139] c = (Ionic content of Cl - in the injection test solution (mg / L)) * (0.05 / 0.5) * 100

[0140] d 滤 = (Ionic content of SO4 2- in the injection test solution (mg / L)) * (0.05 / 0.5) * 100

[0141] e 滤 = (Ionic content of F - in the injection test solution (mg / L)) * (0.05 / 0.5) * 100

[0142] f 滤 = (Ionic content of NO3 - in the injection test solution (mg / L)) * (0.05 / 0.5) * 100

[0143] Number of determinations: Determine in parallel twice and take the average value.

[0144] (4) Determination of the density of the raw water sample and the filtered slurry brine sample (hereinafter simply referred to as the test sample)

[0145] Weigh the dry 100 mL volumetric flask as m1 (unit: mg). Add the test sample cooled to room temperature to the volumetric flask and accurately fill it to the 100 mL mark. Weigh it as m2 (unit: mg). Calculate the density ρ (unit: g / L) of the test sample according to formula (7).

[0146]

[0147] Number of determinations: Determine twice in parallel and take the average value.

[0148] In formula (7):

[0149] ρ is the density of the sample to be measured (g / L)

[0150] m1 is the weight of a dry 100 mL volumetric flask (mg)

[0151] m2 is the weight (mg) when the sample to be measured at room temperature is accurately filled to the graduation line in a 100 mL volumetric flask.

[0152] Example 1 (Basic research)

[0153] Take 100 g of semi-finished ash sample in a 500 mL glass beaker, add 150 mL of raw material water, stir to form a uniform slurry, and take samples in sequence: take raw material water sample, take semi-finished aluminum ash sample, take slurry sample, and filter the slurry sample to obtain a slurry-filtered brine sample; measure the densities of the raw material water sample and the slurry-filtered brine sample, which are ρ 原 is 1061.1 g / L, ρ 滤 is 1202.3 g / L; use ion chromatography to measure the sample, and the measured Cl - content in the semi-finished aluminum ash sample is 154.1 g / Kg; the measured Cl - content in the raw material water sample is 54.2 g / L, the SO4 2- content is 0.62 g / L, the F - content is 0.11 g / L, the NO3 - content is 0.001 g / L; the measured Cl - content in the slurry-filtered brine sample is 153.9 g / L, the SO4 2- content is 2.3 g / L, the F - content is 0.48 g / L, the NO3 - content is 0.003 g / L; substitute the above data into formula (1):

[0154]

[0155] The calculated volume ratio of raw material water to semi-finished aluminum ash is 1.48:1 (the preset volume ratio of raw material water to semi-finished aluminum ash is 150 mL:100 g = 1.5:1), and the error is 1.3% which is less than 5%, so it can accurately reflect the ratio of the true volume of raw material water to the mass of raw material semi-finished aluminum ash. The semi-finished aluminum ash is the powder particles obtained by ball milling and screening the raw material aluminum ash and removing the aluminum-containing particles. The mesh number of the semi-finished aluminum ash particles is less than 80 mesh. The raw material water comes from: after the semi-finished aluminum ash undergoes hydrolysis reaction, it is sent out from the reaction tank, filtered by a filter, and the hydrolysis residue is obtained. The hydrolysis residue is washed with water, and the water used for washing the hydrolysis residue is recycled and used as raw material water. This raw material water contains NaCl; Na2SO4; NaF; NaNO3.

[0156] Regular calibration: Prepare raw material water and semi-finished ash every week, with 3 standard samples of different ingredient ratios. Use this standard to measure and verify whether the results are accurate. The relative error between the measurement result and the ingredient ratio of the standard sample should be ≤ 5%. If it is greater than 5%, immediately find out the reason and conduct the experiment again until it meets the standard.

[0157] Example 2 (pilot scale-up)

[0158] Take 1000 kg of semi-finished ash sample and put it into a stirring tank, add 1500 L of raw material water, stir to form a uniform slurry. Take raw material water sample, take semi-finished aluminum ash sample, take slurry sample, and filter the slurry sample to obtain a slurry-filtered brine sample; measure the densities of the raw material water sample and the slurry-filtered brine sample, which are ρ 原 1068.5 g / L and ρ 滤 1206.8 g / L respectively; use ion chromatography to measure the samples, and the measured Cl - content of the semi-finished aluminum ash sample is 159.2 g / Kg; the measured Cl - content in the raw material water sample is 147.3 g / L, the SO4 2- content is 0.53 g / L, the F - content is 0.12 g / L, and the NO3 - content is 0.001 g / L; the measured Cl - content in the slurry-filtered brine sample is 153.9 g / L, the SO4 2- content is 2.1 g / L, the F - content is 0.41 g / L, and the NO3 - content is 0.002 g / L; Substitute the above data into equation (1):

[0159]

[0160] The calculated ratio of the volume of raw material water to the mass of semi-finished aluminum ash is 1.51:1 (the preset ratio of the volume of raw material water to the mass of semi-finished aluminum ash is 150 mL:100 g = 1.5:1), and the error is 0.6% which is less than 5%, so it can accurately reflect the ratio of the true volume of raw material water to the mass of raw material semi-finished aluminum ash. The semi-finished aluminum ash is the powder particles obtained by ball-milling and screening the raw material aluminum ash and sieving out the aluminum-containing particles. The mesh number of the semi-finished aluminum ash particles is less than 80 mesh.

[0161] The raw material water comes from: after the semi-finished aluminum ash undergoes a hydrolysis reaction, it is sent out from the reaction tank, filtered by a filter, and the hydrolysis residue is obtained. The hydrolysis residue is washed with water, and the water used for washing the hydrolysis residue is recycled and used as raw material water. This raw material water contains NaCl; Na2SO4; NaF; NaNO3.

[0162] Example 3 (Industrial Application)

[0163] In the method for measuring the water-to-ash material ratio of the slurry in the hydrolysis treatment of aluminum ash in this example, it is applied to the patent No. CN202322077555.3, and the utility model name is a precise ratio system for aluminum ash treatment ash water, which is used to monitor the ratio of water and aluminum ash materials in the system in real time and judge whether the ratio system is operating normally.

[0164] When the precise ratio system for ash water is operating, the semi-finished ash feeding speed is 100 kg / minute and enters the stirring tank, and the raw material water feeding speed is 150 L / minute. It is stirred in the stirring tank into a uniform slurry, and the slurry in the stirring tank is sent into the reaction tank by a slurry pump. Take raw material water samples, semi-finished aluminum ash samples, and slurry samples, and filter the slurry samples to obtain slurry-filtered brine samples; measure the densities of the raw material water samples and the slurry-filtered brine samples, which are ρ 原 is 1057.8 g / L, ρ 滤 is 1198.1 g / L; use ion chromatography to measure the samples, and the measured Cl - content in the semi-finished aluminum ash sample is 152.1 g / Kg; the measured Cl - content in the raw material water sample is 51.7 g / L, the SO4 2- content is 0.56 g / L, the F - content is 0.14 g / L, and the NO3 - content is 0.001 g / L; the measured Cl - content in the slurry-filtered brine sample is 151.1 g / L, the SO4 2- content is 2.4 g / L, the F - content is 0.45 g / L, and the NO3 -The content is 0.003 g / L; the ratio of the volume of raw water to the mass of semi-finished aluminum ash obtained according to formula (1) is 1.47 (the preset ratio of the volume of raw water to the mass of semi-finished aluminum ash is 150 mL:100 g = 1.5:1), and the error is 2% which is less than 5%, so it can accurately reflect the ratio of the true volume of raw water to the mass of raw semi-finished aluminum ash, meeting the actual production needs. The semi-finished aluminum ash is the powder particles obtained by ball-milling and screening the raw aluminum ash and removing the aluminum-containing particles, and the mesh number of the semi-finished aluminum ash particles is less than 80 mesh. The raw water comes from: after the semi-finished aluminum ash undergoes a hydrolysis reaction, it is sent out from the reaction tank, filtered by a filter, and the hydrolysis residue is obtained. The hydrolysis residue is washed with water, and the water used for washing the hydrolysis residue is recycled and used as raw water, and this raw water contains NaCl; Na2SO4; NaF; NaNO3.

[0165] In Example 3, the ratio of the volume of raw water to the mass of semi-finished aluminum ash measured in the batching tank is 1.47, and this measured value is within the normal range of 1.4 - 1.6 for the ratio of the volume of raw water to the mass of semi-finished aluminum ash. At this time, the ash-water precise proportioning system operates normally.

[0166] Regularly use the method for measuring the water-ash material ratio of the slurry in the hydrolysis treatment of aluminum ash in this application to detect the water-ash material ratio V 原 / M of the volume of raw water to the mass of semi-finished aluminum ash in the mixing tank:

[0167] When the V 原 / M ratio range is between 1.4 - 1.6, it indicates that the ash-water precise proportioning system operates normally;

[0168] When the V 原 / M ratio range is greater than 1.6 or less than 1.4, it indicates that the ash-water precise proportioning system does not operate normally. Stop feeding, detect the ash-water precise proportioning system, calibrate the feeding weight of semi-finished ash and the water inflow of raw water, and after calibration and stabilization, take samples again for analysis and detection of the V 原 / M ratio; if the V 原 / M ratio range is between 1.4 - 1.6, it indicates that the ash-water precise proportioning system operates normally after adjustment; if the V 原 / M ratio range is still greater than 1.6 or less than 1.4, repeat the above adjustment steps until the V 原 / M ratio range is within 1.4 - 1.6 and the ash-water precise proportioning system operates normally.

[0169] Comparative example

[0170] Before using the method for measuring the water-to-ash material ratio of the slurry in the hydrolysis treatment of aluminum ash of the present invention, the filter cake weighing method was used to measure the mass ratio of aluminum ash to water. Specifically, the semi-finished ash was fed at a rate of 100 kg / min (salt mass percentage content 26%) into the stirring tank, and the raw water was added at a rate of 150 L / min to be stirred into a slurry. A semi-finished ash sample was taken at the feed inlet of the stirring tank to analyze the salt content. About 200 ml of the slurry sample in the stirring tank was taken at the sewage outlet of the stirring tank with a plastic measuring cup, and the gross weight M_mao was weighed. The slurry was filtered with a vacuum filter, the measuring cup was cleaned, dried and weighed to obtain the weight of the measuring cup M_cup. All the washed-out slurry was filtered on the vacuum filter, and the filter cake was rinsed 3 times with pure water and filtered until no liquid dripped from the bottom of the funnel. The filter cake was taken out, dried at 110°C for 2 h, and the dry filter cake weight M 饼 ,

[0171] Then the weight of the original semi-finished ash corresponding to the dry filter cake is M 饼 / (1 - salt content%);

[0172] The weight of water in the slurry is M 毛 - M 杯 - M 饼 / (1 - salt content%)

[0173] The mass ratio of water to aluminum ash is: [M 毛 - M 杯 - M 饼 / (1 - salt content%)]: [M 饼 / (1 - salt content%)]

[0174] Comparative example 1, comparative example 2 and comparative example 3 are three samplings of measuring the ratio of aluminum ash to water by the filter cake method. The results are shown in Table 2 below. Since the filter cake weighing method measures the ratio of water mass to aluminum ash mass, and in the production process, the raw water is often calculated by flow rate to measure the consumption of raw water. Therefore, when the preset ratio of raw water to semi-finished aluminum ash is the ratio of the volume of raw water to the mass of semi-finished aluminum ash, the units are not unified and need to be converted. The ρ 原 of raw water is 1057.8 g / L

[0175] Table 2: Measuring the ratio of the volume of raw water to the mass of semi-finished aluminum ash by the filter cake weighing method

[0176]

[0177] As can be seen from Table 2, for Comparative Example 1, Comparative Example 2, and Comparative Example 3, when using the filter cake weighing method to measure the ratio of the volume of raw material water to the mass of semi-finished aluminum ash, there are obvious deviations compared with the true ratio of the volume of raw material water to the mass of semi-finished aluminum ash of 1.5:1. The error is greater than 5%, and the measured value deviation is on the high side, which cannot accurately reflect the true ratio of the volume of raw material water to the mass of semi-finished aluminum ash. The ratio of the volume of raw material water to the mass of semi-finished aluminum ash in production is within the normal ratio range of 1.4 - 1.6, but the measured ratio is outside the normal ratio range of 1.4 - 1.6. When adjusting according to this ratio, there will be too little raw material water in the mixing tank during the production process; there is too little water in the slurry, and the soluble salts in the aluminum ash cannot be completely dissolved in the raw material water, and the aluminum ash and water cannot form a slurry, and the aluminum ash will agglomerate, which may seriously cause pipeline blockage and make the production unable to proceed. Less raw material water means a relatively high concentration of reactants, which may lead to an accelerated reaction rate and too violent reaction. In the reaction tank, if the reaction is too violent, a large amount of heat and gas may be generated, increasing the risk of explosion and equipment damage and affecting the safety of the mixing tank.

[0178] However, the comparison results of the measurement method of the present application and the filter cake weighing method are shown in Table 3.

[0179] As can be analyzed from Table 3, when the proportioning equipment is operating normally, the ratio of the volume of raw material water to the mass of semi-finished aluminum ash is measured by using two measurement methods. The ratio of raw material water to the mass of semi-finished aluminum ash measured by the method of the present invention is closer to the preset ratio value, and can accurately measure the ratio of the volume of raw material water to the mass of semi-finished aluminum ash in the slurry of the mixing tank, correct the material ratio of raw material water and semi-finished aluminum ash in actual production, and ensure the accuracy of actual production.

[0180] Table 3 Measurement of the ratio of the volume of raw material water to the mass of semi-finished aluminum ash by the filter cake weighing method and the chloride ion analysis method

[0181]

[0182] Example 4

[0183] First, calibrate the feeding weight of semi-finished ash and the water inflow of raw material water. After accurate calibration, adjust the feeding speed of semi-finished ash to 100 kg / min into the mixing tank, and the feeding speed of raw material water is 300 L / min. Stir in the mixing tank to form a uniform slurry, and use a slurry pump to send the slurry in the mixing tank into the reaction tank. Take samples in sequence: take raw material water samples, take semi-finished aluminum ash samples, take slurry samples, and filter the slurry samples to obtain slurry filtered brine samples; measure the densities of the raw material water samples and the slurry filtered brine samples, which are ρ 原 is 1057.2 g / L, ρ 滤 is 1110.2 g / L; use ion chromatography to measure the samples, and measure the Cl in semi-finished aluminum ash -The content is 152.1 g / Kg; the Cl content in the raw water sample was measured - The content is 51.8 g / L, and the SO4 2- The content is 0.56 g / L, and the F - The content is 0.14 g / L, and the NO3 - The content is 0.001 g / L; the Cl content in the filtered brine sample of the slurry was measured - The content is 101.1 g / L, and the SO4 2- The content is 1.45 g / L, and the F - The content is 0.28 g / L, and the NO3 - The content is 0.002 g / L;

[0184] Substitute the above data into equation (1):

[0185]

[0186] The calculated ratio of the volume of raw water to the mass of semi-finished aluminum ash is 2.96:1 (the actual ratio of the volume of raw water to the mass of semi-finished aluminum ash is 300 mL:100 g = 3:1), and the error is 1.3% which is less than 5%, so it can accurately reflect the ratio of the actual volume of raw water to the mass of raw semi-finished aluminum ash and meet the needs of actual production. The semi-finished aluminum ash is the powder particles obtained by ball-milling and screening the raw aluminum ash and removing the aluminum-containing particles, and the mesh number of the semi-finished aluminum ash particles is less than 80 mesh.

[0187] The raw water comes from: after the semi-finished aluminum ash undergoes a hydrolysis reaction, it is sent out from the reaction tank and filtered by a filter to obtain hydrolysis residues. The hydrolysis residues are washed with water, and the water used for washing the hydrolysis residues is recycled and used as raw water, and this raw water contains NaCl; Na2SO4; NaF; NaNO3.

[0188] Example 5

[0189] First, calibrate the feeding weight of the semi-finished ash and the water inflow of the raw water. After accurate calibration, adjust the feeding speed of the semi-finished ash to 100 kg / min and enter the stirring tank, and the feeding speed of the raw water is 500 L / min. Stir in the stirring tank to form a uniform slurry, and use a slurry pump to send the slurry in the stirring tank into the reaction tank. Take raw water samples, semi-finished aluminum ash samples, and slurry samples, and filter the slurry samples to obtain filtered brine samples of the slurry; measure the densities of the raw water samples and the filtered brine samples of the slurry, which are ρ 原 is 1057.3 g / L, and ρ 滤 is 1089.3 g / L; use ion chromatography to measure the samples, and the Cl content in the semi-finished aluminum ash is measured - The content is 152.1 g / Kg; the Cl content in the raw water sample was measured - The content is 51.8 g / L, and the SO42- The content is 0.56 g / L, F - The content is 0.14 g / L, NO3 - The content is 0.001 g / L; the Cl in the filtered brine sample of the slurry is measured - The content is 80.5 g / L, SO4 2- The content is 1.08 g / L, F - The content is 0.15 g / L, NO3 - The content is 0.002 g / L; substituting the above data into equation (1):

[0190]

[0191] The calculated ratio of the volume of raw water to the mass of semi-finished aluminum ash is 5.12:1 (the actual ratio of the volume of raw water to the mass of semi-finished aluminum ash is 500 mL:100 g = 5:1), and the error is 2.4% which is less than 5%, so it can accurately reflect the ratio of the actual volume of raw water to the mass of raw semi-finished aluminum ash and meet the actual production needs. The semi-finished aluminum ash is the powder particles obtained by ball-milling and screening the raw aluminum ash and removing the aluminum-containing particles. The mesh number of the semi-finished aluminum ash particles is less than 80 mesh.

[0192] The raw water comes from: after the hydrolysis reaction of the semi-finished aluminum ash, it is sent out from the reaction tank, filtered by a filter, and the hydrolysis residue is obtained. The hydrolysis residue is washed with water, and the water used for washing the hydrolysis residue is recycled and used as raw water. This raw water contains NaCl; Na2SO4; NaF; NaNO3.

[0193] Examples 1 - 5: Summarized as shown in Table 4 below.

[0194] Table 4 Comparison of the ratio of the volume of raw water to the mass of raw semi-finished aluminum ash in Examples 1 - 5, and the ratio of the actual value to the preset ratio:

[0195]

[0196] It can be seen from Table 4 that under different ratios of the volume of raw water to the mass of raw semi-finished aluminum ash, the method of this application for measuring the ratio of the volume of raw water to the mass of raw semi-finished aluminum ash in the slurry is relatively accurate, and the difference from the ratio of the volume of raw water to the mass of raw semi-finished aluminum ash set in the actual feeding is not large. The measurement method of this application can accurately reflect the ratio of aluminum ash to water set in the actual feeding and meet the actual production needs.

[0197] The above-described embodiments are only preferred embodiments of the present invention, and are merely used to explain the present invention, not to limit the scope of implementation of the present invention. For those skilled in the art of this technology, of course, other implementation manners can be easily made by means of substitution or change according to the technical content disclosed in this specification. Therefore, all changes and improvements made on the principle of the present invention shall be included within the scope of the patent application of the present invention.

Claims

1. A method for determining the water-to-ash material ratio of the slurry in the hydrolysis treatment of aluminum ash, characterized in that, It includes the following steps: S1: Feed raw water and semi-finished aluminum ash into a stirring tank according to a preset material ratio for mixing to obtain a slurry, and then send the slurry into a reaction tank for hydrolysis reaction of the semi-finished aluminum ash; after the reaction is completed, the remaining slurry is discharged from the reaction tank, and the solid-liquid separation of the reacted slurry is carried out to obtain hydrolysis residues and filtered brine; The semi-finished aluminum ash is powder particles obtained by ball milling and screening the raw aluminum ash and screening out aluminum-containing particles; The hydrolysis residues are washed with water, and the water after washing is used as raw water; S2: Sampling is carried out in sequence: taking a raw water sample, taking a semi-finished aluminum ash sample, and taking a slurry sample; The slurry sample is filtered to obtain a slurry filtered brine sample; S3: Measure the Cl - content in the semi-finished aluminum ash sample; Measure the density of the raw water sample and determine the mass concentrations of Cl - , SO4 2- , F - , NO3 - in the raw water sample; Measure the density of the filtered brine sample of the slurry; and measure the mass concentrations of Cl - , SO4 2- , F - , NO3 - in the filtered brine sample of the slurry; S4: Substitute the value measured in S3 into formula (1) to obtain the volume of raw material water and the mass ratio of semi-finished aluminum ash in the stirring tank as V 原 / M: In formula (1): V 原 is the volume (L) of raw water in the mixing tank; M is the weight (Kg) of semi-finished ash in the mixing tank; a is the Cl - ion content (g / Kg) in the semi-finished ash; ρ 原 is the density (g / L) of the raw water sample; b is the Cl - ion content (g / L) in the raw water; d 原 is the SO4 2- ion content (g / L) in the raw water; e 原 is the F - ion content (g / L) in the raw water; f 原 is the NO3 - ion content (g / L) in the raw water; ρ 滤 is the density (g / L) of the slurry-filtered brine sample; c is the Cl - ion content (g / L) in the slurry-filtered brine; d 滤 is the SO4 2- ion content (g / L) in the slurry-filtered brine; e 滤 is the F - ion content (g / L) in the slurry-filtered brine; f 滤 is the NO3 - ion content (g / L).

2. The method for determining the water-to-ash material ratio of the slurry in the hydrolysis treatment of aluminum ash according to claim 1, characterized in that, The mesh number of the semi-finished aluminum ash particles is less than 80 mesh.

3. The method for determining the water-to-ash material ratio of the slurry in the hydrolysis treatment of aluminum ash according to claim 1, characterized in that, The ratio of the volume of raw water to the mass of semi-finished aluminum ash in the preset ratio is 1.5:

1.

4. The method for determining the water-to-ash material ratio of the slurry in the hydrolysis treatment of aluminum ash according to claim 1, wherein The Cl in the semi-finished aluminum ash sample - content, Cl in the raw material water sample - , SO4 2- , F - , NO3 - mass concentration, and Cl in the slurry filtration brine sample - , SO4 2- , F - , NO3 - The determination method of the mass concentration is all carried out by ion chromatography.

5. Application of a method for determining the water-to-ash material ratio of a slurry in the hydrolysis treatment of aluminum ash according to any one of claims 1-4 in a water-ash batching system during the hydrolysis treatment of aluminum ash.

6. The application according to claim 5, characterized in that When the V 原 / M ratio ranges from 1.4 to 1.6, it indicates that the water-cement batching system is operating normally; When the V 原 / M ratio range is greater than 1.6 or less than 1.4, it indicates that the water-cement batching system is operating abnormally. Stop feeding, detect the water-cement batching system, calibrate the semi-finished product ash discharge weight and the raw material water inflow, and take another sample for analysis and detection of the V 原 / M ratio after the calibration is stable; if the V 原 / M ratio range is between 1.4 and 1.6, it indicates that the water-cement batching system is operating normally after adjustment; if the V 原 / M ratio range is still greater than 1.6 or less than 1.4, repeat the above adjustment steps until the V 原 / M ratio range is within 1.4 - 1.6 and the water-cement batching system is operating normally.

Citation Information

Patent Citations

  • Ash water accurate proportioning system for aluminum ash treatment

    CN220759189U